215 WHAT VALUE DOES OCCUPATIONAL THERAPY ADD TO THE EDITH (EMERGENCY DEPARTMENT IN THE HOME) SERVICE?. (25th October 2022) - Davis, AJ; Delaney, A; Doyle, C; Sweeney, A; Nally, SM; Namara, RM
Abstract: Background: The EDITH team has provided an alternative care pathway for older adults with emergency care that takes place in the persons' home. The EDITH service provides both medical and Occupational Therapy assessment and intervention in the home environment with onward referrals to appropriate agencies as indicated, thus negating the need for an emergency department presentation. Methods: To assess consistency in OT practice and assessment, an audit was completed of OT logbooks and electronic patient data. Paper count method was used. Data gathered with regards to OT process and assessment. Results: 100% of patients had at least 1 type of OT assessment (e.g functional, home environment, falls prevention, cognitive etc), 80% had at least 2 and 43% had 3 or more types of OT assessments. 100% of patients had Clinical Frailty Scores completed, 100% had their living situation and level of care supports assessed and documented. 43% of patients received onwards referrals to community supports, day hospital, voluntary supports etc. Conclusion: The OTs complete a thorough and multifactorial assessment of the older adult within the context of their home environment. This holistic assessment approach adds significant value to the overall EDITH assessment and service. It also ensures appropriate and relevant onwards referrals are completed. It is imperative to ensure value for money with regards to health care services. In line with the HSE "Value Improvement Programme" it is timely to review OT services and ensure they are delivering consistent, high quality and high value services for our stakeholders.